The principle of Legality in the Criminal law in the Case law of The European Court of Human Rights - Assistant Professor Dr Rafid Khayun Debisan (The college of law and political science journal, 2025)
The principle of the legality of crimes and punishments became consistent with the modern penal code, and there is no doubt that it emerged at the invitation of many philosophers of the Age of Enlightenment, who paid great attention to it, so it began to be coherent in the Russian, American and French penal code, and with the passage of time it came He became mature and prosperous, and inclined to adhere to covenants. universality and international agreements, following World War II, until they became a prominent principle, It joins the first paragraph of Article Seven, and hides in the shadow of the shadow of the European Convention on Human Rights.(The principle of the legality of crimes and punishments in the case law of the European Court of Human Rights), in order to clarify the significance attached to the purposes of its definition, and to clarify the justifications for its coverage and inclusion in its aspects, and because of Article M A study that supports the preparation of scientific research that supports the theory of this principle in the legal lesson.